Reis door mijn kamer - de Maistre, Xavier; De Bruin, Paul; De Maistre, Xavier (Breda : Ignatius Ziekenhuis, 1995)
Mol, Pieter Laurens ; Toebosch, Moniek ; Bolink, Merijn ; van der Kraan, Helena ; De Bruyn, Goele ; Fleury, Sylvie ; Claassen, Tom ; Bloom, Barbara ; Hout, Ronald in 't ; Copers, Leo ; Kabakov, Ilya ; Schuil, Han ; Vos, Jan ; Fritz, Katharina ; François, Michel ; Trockel, Rosemarie
Nederlands
boek